Ecclesiological elements in the theology of St. Bonaventure - Zamora, Angelina Magdalena (Tesi gregoriana, 2020)
While Bonaventure's theology was of renewed interest in the twentieth century, the vast majority of studies focus on his Trinitarian theology, his Christology and his mystical doctrine. This text demonstrates the ecclesiology implicit within Bonaventure's theology, especially in his Commentary on the Sentences of Peter Lombard and the Breviloquium. Using Bonaventure's sacramental doctrine as a foundation, it relies on the images with which Bonaventure speaks of the Church as "points of entry" into his ecclesiology, with a special concern to identify Trinitarian and Pneumatological elements present in his ecclesiology. Most surprising was Bonaventure's sacramental doctrine regarding Confirmation and Extreme unction. The conclusions offer responses to questions like: "how well does Bonaventure balance the Pneumatological and Juridical elements within his ecclesiology?" and "How Franciscan is his ecclesiology?"